Peng' You Caterer Sdn Bhd/ Mohamad Zarir Mohamad Khozali... [et al.] - Mohamad Khozali, Mohammad Zarir; Hashim, Ridzuan; Johari Johar, Azizul Hakim; Alwi, Zoradyah; Md Zain, Siti Hartini (2000)
Peng' You Caterer Sdn Bhd is a catering company that provide catering packages in Alor Setar , Kedah. They started their business in 1st January 2002. The type of their business is partnership (Sdn Bhd).